SCIENTIFIC PSYCHOLOGICAL APPROACHES TO TESTING PHYSICAL FITNESS OF ATHLETES - Lutfullaev Bunyod Ismatovich (Journal Park Publishing, 2023)
This article contains scientific psychological approaches to testing the physical fitness of athletes.
Keywords: scientific approach, psychological approach, psychophysiological factors.